The Internet giants and the future of the liability legal regime applicable to the technical intermediaries in the European and French Law - Clément-Fontaine, Mélanie (Law, State and Telecommunications Review, 2019)
Purpose ”“ The article brings an examination of the legal regime of civil liability of the content and stockage Internet providers (technical intermediaries) under the European and French law in order to evaluate the possibilities of a new regulatory design, which may provide a better balance between the rights and obligations of those technical intermediaries. Methodology/approach/design ”“ The research uses legal articles and rulings to provide an analysis of the European and French regarding the civil liability of the technical intermediaries to assess the limits of the current legal regulatory regime. Findings ”“ Extracting data from rulings, technical reports and academic legal texts, the article shows the possibility of legal construction of new regulatory means that may provide a better balance between rights and obligations of the technical intermediaries.